(untitled) (International Journal of Latest Technology in Engineering Management & Applied Science, 2025)
Social media platforms such as Facebook, Instagram, and WhatsApp have emerged as crucial tools for rural business promotion. These platforms provide low-cost, high-reach avenues for marketing, customer engagement, and brand building. This paper examines the adoption, usage patterns, benefits, and challenges of social media for rural entrepreneurs. Using a mixed-method approach combining surveys and secondary research, the study finds that WhatsApp is the most popular platform for direct communication and order management, Facebook is effective for community engagement and marketplace visibility, and Instagram is increasingly used for visual branding and targeting younger customers. The paper concludes with recommendations for digital literacy training, infrastructural support, and integrated marketing strategies to maximize rural business growth.